Use of Autologous Platelet Gel in Bariatric Surgery - Brady, Chad (J Extra Corpor Technol, 2006)
Gastric bypass surgery is a common corrective procedure for obesity that is associated with many risks. Recent studies describing the use of autologous platelet gel (APG) have shown promise in preventing certain operative complications and improved healing processes. These improvements have been credited to the concentrated platelets and growth factors present in APG, as well as the native concentrations of fibrinogen. There are numerous applications for the use of APG in surgery, and the list continues to expand. However, little research exists to support the efficacy of APG in bariatric surgery. This case series describes using APG with patients undergoing laparoscopic Roux-en-Y gastric bypass surgery.